Sustainability as Strategic Communication: Evidence from the Turkish Textile Industry - Enginkaya, Ebru; Ozer Cizer, Ece; Yurdakul, Kameri (MDPI, 2026)
This study examines how sustainability is discursively constructed, prioritized, and selectively institutionalized in the Turkish textile and apparel sector, conceptualizing sustainability reporting not only as an operational practice but also as a form of strategic communication. Drawing on the Triple Bottom Line framework, stakeholder theory, and institutional theory, it employs a theory-informed thematic content analysis of publicly available sustainability-related disclosures from 52 firms operating between 2020 and 2024. Rather than treating these documents as direct representations of organizational practices, the study approaches them as institutionalized communicative artifacts through which firms signal legitimacy, position themselves in relation to key external audiences, and justify particular sustainability orientations. The findings indicate a pronounced institutionalization of environmental narratives, while social and economic dimensions remain comparatively weakly embedded, particularly among small and domestically oriented firms. This imbalance appears to be structurally reproduced through reporting standards, market pressures, and certification regimes that selectively reward environmental compliance. The analysis further suggests that firms cluster into distinct sustainability profiles, reflecting differentiated pathways of institutional alignment rather than a uniform transition process. Theoretically, the study help explains why certain sustainability dimensions become prioritized over others. Empirically, it provides a comparative mapping of firm-level sustainability orientations in an emerging economy context. By conceptualizing sustainability as a signaling and positioning mechanism, the study contributes to marketing and sustainability literature by highlighting how corporate disclosures function as tools of legitimacy construction rather than neutral representations of practice.
Keywords: sustainability; textile industry; environmental sustainability; economic sustainability; social sustainability; thematic analysis; CORPORATE SOCIAL-RESPONSIBILITY; CIRCULAR ECONOMY; MODEL; SMES; Science & Technology - Other Topics; Environmental Sciences & Ecology